REVITALIZING THE ISLAMIC EDUCATION CURRICULUM WITH A CONTEXTUAL APPROACH AT SD NEGERI 004 CEMAGA SELATAN - Anizar, Anizar; Hasmiza, Hasmiza; Syahroni, Said Ali; Wan Chik, Wan Mohd Yusof (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study explores the development of contextual approach-based Islamic Religious Education (PAI) teaching materials and their impact on students' critical thinking skills at SD Negeri 004 Cemaga Selatan. Method: Using a qualitative approach, data were collected through participatory observation, interviews, and document analysis, then analyzed using the Miles and Huberman model with triangulation for credibility. Result: Findings reveal that contextual teaching materials developed through systematic stages, needs analysis, design, and evaluation, effectively enhance critical thinking through project-based and transformative learning. Teachers act as facilitators, connecting learning content to real-world contexts, which improves student understanding, motivation, and critical awareness. However, time constraints, limited resources, and conventional learning habits pose implementation challenges. Conclusion: The study concludes that contextual and inclusive teaching materials foster critical thinking and character development aligned with contemporary societal needs, contributing to more effective and relevant educational practices that improve overall education quality.